Analysis of the Use of Figurative Language in Taylor Swift's Song Lyrics - Rahmawati, Astri Rahayu (Critical Review of English-Arabic World Journal, 2025)
This study aims to describe the types of figurative language and connotative meanings contained in four Taylor Swift songs, "Blank Space," "Love Story," "All Too Well," and "Cardigan." This study uses a qualitative descriptive method with documentation techniques that involve reading the lyrics as a whole, recording parts that contain figurative language, and analyzing them from the perspective of stylistic theory and connotative meaning. The research findings show that Taylor Swift consistently uses a variety of language styles, such as metaphors, similes, personifications, hyperbole, symbolism, and allusions. The use of figurative language serves to reinforce the emotional and aesthetic messages of the lyrics, especially those related to themes of love, inner conflict, nostalgia, and the healing process. Thus, language style is an important element that enriches the conveyance of meaning in Taylor Swift's musical works.